Acculturation Scale to Russia for Chinese Students: Development and Psychometric Verification - Irina A. Novikova; Alexey A. Novikov; Dmitriy A. Shlyakhta (Peoples' Friendship University of Russia (RUDN University), 2021)
The topic on diagnosing intercultural adaptation and psychological acculturation to a new socio-cultural environment is relevant in connection with the processes of globalization and, in particular, with the growth of academic mobility in education. Research on this problem are especially relevant for Russian science due to the lack of acculturation scales, which are widely represented in Western and international psychology. In 2019, a research team led by Professor A. Ardila developed the Russian-language Acculturation Scale for Russia (ASR), which was validated on a sample of international university students from 71 countries of the world. The aim of the present study was to adapt the ASR for the Chinese students studying in Russian universities. Chinese students are the largest group of international students from far abroad studying at Russian universities, while many of them experience significant difficulties in adapting to a new socio-cultural environment, as well as in learning the Russian language. In total, the study involved 213 Chinese students (59% - female) studying at Russian universities, of which 93 students (58% - female) completed the Russian-language version of the ASR, and 118 students (61% - female) completed the Chinese version of the ASR, which was designed using the back translation. Both ASR versions were psychometrically tested using Cronbachs and MacDonalds coefficients, as well as bifactorial analysis. The methods of descriptive statistics and the Wilcoxon W-test were used to compare the Russian-language and Chinese versions of the ASR. The normalization was carried out by means of non-linear percentile normalization (stanines). As a result, a high consistency of the Russian-language and Chinese versions of the ASR and their equivalence with each other were shown. Both versions can be used to assess the level of acculturation of Chinese students to Russia, while the Chinese version is recommended for the Chinese students who have been living in Russia for less than 1-1.5 years and/or have a poor Russian proficiency.